Management of Concomitant Severe Thermal Injury and ST-Elevation Myocardial Infarction - Julie Beveridge; Curtis Budden; Abelardo Medina; Kathryne Faccenda; Shawn X. Dodd; Edward Tredget (MDPI AG, 2024)
Acute coronary thrombosis is a known, but rare, contributor to morbidity and mortality in patients with thermal and electrical injuries. The overall incidence of myocardial infarction among burn patients is 1%, with an in-hospital post-infarction mortality of approximately 67%, whereas the overall mortality rate of the general burn patient population is from 1.4% to 18%. As such, early detection and effective peri-operative management are essential to optimize patient outcomes. Here, we report the details of the management of an adult male patient with a 65% total body surface area severe thermal injury, who developed an ST-elevation myocardial infarction (STEMI) in the resuscitation period. The patient was found to have 100% occlusion of his left anterior descending coronary artery, for which prompt coronary artery stent placement with a drug-eluting stent (DES) was performed. Following stent placement, the patient required dual antiplatelet therapy. The ongoing dual antiplatelet therapy required the development of a detailed peri-operative protocol involving pooled platelets, packed red blood cells, desmopressin (DDAVP™) and intraoperative monitoring of the patient's coagulation parameters with thromboelastography for three staged operative interventions to achieve complete debridement and skin grafting of his burn wounds.